PEMBERDAYAAN GENDER, PENDAPATAN PEREMPUAN DAN PENURUNAN KEMISKINAN: BUKTI DATA PANEL DARI KAWASAN BARAT INDONESIA - Gunawan Adnan; Khairul Amri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
The purpose of this study is to analyze the effect of gender empowerment on women's income and poverty reduction and examine the role of women's income as a mediating variable between gender empowerment and poverty reduction. This study uses panel data of 8 provinces from western Indonesia during the period 2010-2018. Hierarchical linear panel regression (HLPR) is employed to investigate the effect of gender empowerment on women's income and poverty reduction. Sobel test examines the role of women's income in mediating the effect of women's income on poverty reduction. Granger causality test is used to analyze the direction of causality between the three variables. The study points out that gender empowerment has a positive and significant effect on women's income but did not affect poverty reduction. Women's income has a negative and significant impact on the poverty rate. The existence of women's income mediates the effect of gender empowerment toward poverty reduction. The role of women's income mediates the relationship between the two variables is full mediation. Granger causality tests indicate that there is unidirectional causality from gender empowerment to women's income, and from poverty rate to gender empowerment.